1999
DOI: 10.1021/la980824i
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Azo Dyes with Cationic Amphiphiles at Low Concentrations in Aqueous Solution

Abstract: The aggregation of a series of n-alkyltrimethylammonium bromide (C n TAB, n = 10, 12, 14, 16, and 18) and 4-n-alkyl-1-methylpyridinium iodide amphiphiles (C m pyI, m = 8, 10, 12, and 14) induced by low concentrations of azo dyes in aqueous solution has been investigated by means of ultraviolet (UV) spectroscopy. It was observed that aggregation takes place at surfactant concentrations far below the cmc of C12TAB, C14TAB, C16TAB, and C18TAB with methyl orange (MO), ethyl orange (EO), and para-methyl red (pMR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
80
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 70 publications
14
80
2
1
Order By: Relevance
“…The nature of spacers has also a large influence on the aggregation of geminis. But, it has been reported that the spacer length hardly affects dyeesurfactant aggregation for 12-s-12, s Z 4,8,12 [5]. Regardless of the effect of different pH and measuring method, it can be concluded that in geminis with two methylene groups in their spacer, the aggregation with anionic dyes such as MO is higher than in other species.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The nature of spacers has also a large influence on the aggregation of geminis. But, it has been reported that the spacer length hardly affects dyeesurfactant aggregation for 12-s-12, s Z 4,8,12 [5]. Regardless of the effect of different pH and measuring method, it can be concluded that in geminis with two methylene groups in their spacer, the aggregation with anionic dyes such as MO is higher than in other species.…”
Section: Resultsmentioning
confidence: 97%
“…In the case of 12-s-12 geminis, short spacers (s Z 2,3) induce the formation of wormlike micelles; geminis with intermediate spacers (s Z 4e12) form spheroidal micelles and vesicles are formed when s Z 16,20 [5]. hypsochromic shift which is about 45e55 nm is in the presence of DTAB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactants are used as auxiliaries in most textile finishing processes such as washing, wetting, dispersing, dyeing and finishing. Also, the interaction between dyes and surfactants have been studied to provide some insight into small molecule-macromolecule interactions, which is of major importance in biochemistry [14].…”
Section: Introductionmentioning
confidence: 99%